Neglected tropical diseases and environment, climate change and ecology - Utzinger, Jürg (Henry Stewart Talks, 2021)
Neglected tropical diseases (NTDs), The life cycle of schistosomiasis, Social-ecological systems and schistosomiasis, Global distribution of schistosomiasis, The impact of environmental factors on schistosomiasis transmission, The impact of climate change on schistosomiasis in China